Churchill, America and Vietnam, 1941-45 - Smith, T. O. (Palgrave Macmillan, 2011)
Put in the wider context of British imperial and diplomatic aims in 1941-1945, the book clarifies the importance of Vietnam to Britain's regional objectives in Southeast Asia; concluding that Churchill was willing to sacrifice French colonial interests in Vietnam for his all-important 'special relationship' with the United States.